Effectiveness of the Mindfulness-Based Stress Reduction Program on Quality of Life and Stress in Individuals with Panic Disorder - Mashhadi Ebrahim, Zahra; Nikroo, Soheila; Atashani kouchesfahani, Armaghan; Hasannezhad Shahsavandi , Zahra; Barekat, Arsalan (Iranian Journal of Neurodevelopmental Disorders, 2026)
Purpose: The objective of this study was to evaluate the effectiveness of a Mindfulness-Based Stress Reduction (MBSR) program on reducing stress and improving quality of life among individuals diagnosed with panic disorder.Methods and Materials: This quasi-experimental study utilized a pretest–posttest design with a control group and included 40 participants diagnosed with panic disorder who were recruited through convenience sampling from a psychotherapy center in Tehran in 2025. Participants were randomly assigned to either the experimental group, which received eight weekly sessions of MBSR, or the control group, which received no intervention. Data were collected using the Perceived Stress Scale and the WHOQOL-BREF quality-of-life questionnaire. Statistical analyses were performed in SPSS 26 using repeated-measures ANOVA, with assumptions of normality, sphericity, and homogeneity tested prior to main analyses.Findings: Repeated-measures ANOVA indicated significant time effects for both quality of life (F = 43.16, p < .001, η² = .662) and stress (F = 25.35, p < .001, η² = .535), along with significant group effects for quality of life (F = 7816.80, p < .001, η² = .897) and stress (F = 3083.40, p < .001, η² = .761). Significant time × group interactions were observed for quality of life (F = 35.73, p < .001, η² = .619) and stress (F = 31.15, p < .001, η² = .586). Bonferroni post hoc tests revealed significant improvements from pretest to posttest and pretest to follow-up in both outcomes (p < .001).Conclusion: The findings indicate that mindfulness-based stress reduction is an effective intervention for lowering stress and improving quality of life in individuals with panic disorder, with beneficial effects sustained at follow-up.